Sample survey theory - Raj Des; Chandhok Promod (New Delhi Narosa, 1998)
This book presents the theory that lies behind the sampling method. Chapter 1 introduces the elementary probability & statistical estimation. Chapter 2 offers background information concerning the work of a sampling statistician in the field. Chapter 3 p
Replacement copy of old acc no 75721
Keywords: Sample survey; Sampling(Statistics)